Genesis of the education system in the context of the wave theory of E. Toffler - Roman A. Romashov; Dmitry A. Lipinsky; Aleksandra A. Musatkina; Alexsey A. Stankin; Olga E. Surkova (Revista on line de Política e Gestão Educacional)
The purpose of the research is to determine the patterns of development of the system of Russian and foreign education in the context of scientific approaches to the typology of the state. Consider the features of the genesis of education in the wave theory of socio-cultural development of E. Toffler. Methodology: in the process of research, methods of comparative analysis, cyclicity, intersectoral synthesis, theoretical and legal modeling, historical and legal reconstruction, as well as other methods of scientific knowledge were used. Education, as a product of the State and an instrument of State influence on the consciousness and behaviour of the population, is directly dependent on the peculiarities of the State structure and the objectives of which the State is guided in the process of organizational and managerial activity, the methods of interaction of the State with society, local social corporations and individual citizens/subjects.